Neonatal brain and physiological reactivity in preschoolers: An initial investigation in an Asian sample. (February 2022) - Tsotsi, Stella; Rifkin-Graboi, Anne; Borelli, Jessica L.; Chong, Yap Seng; Rajadurai, Victor Samuel; Chua, Mei Chien; Broekman, Birit; Meaney, Michael; Qiu, Anqi
Abstract: Parasympathetic nervous system (PNS) activity is important to physiological regulation. Limbic structures are important in determining what information the PNS receives, potentially influencing concurrent physiological responsivity and, ultimately, shaping PNS development. Yet, whether individual differences in these structures are linked to PNS activity in early childhood remains unclear. Here, in an exploratory capacity, we examined the association between neonatal limbic structures (i.e., the left and right amygdala and hippocampus) and preschoolers' resting-state respiratory sinus arrhythmia (RSA). RSA is a measure of heart-rate variability, a physiological marker that reflects fluctuation in the PNS and is often found predictive of emotion regulation and psychological wellbeing. Data were extracted from the "Growing Up in Singapore towards Healthy Outcomes" (GUSTO) cohort ( n = 73, 39 girls). Neonatal limbic volume was collected within two weeks after birth while infants were asleep. Resting-state RSA was collected during a coloring session at 42 months of age. After controlling for potential confounders, a Bonferroni-corrected significant association between neonatal left hippocampal volume and resting-state RSA emerged wherein larger hippocampal volume was associated with higher resting-state RSA. No significant associations were present between resting-state RSA and right or left amygdala, or right hippocampal volume. These findings contribute to an increasing body of evidence aiming at enhancing our understanding of neurobiological underpinnings of parasympathetic activity and modulation. Results are also discussed with reference to ideas concerning biological sensitivity to context, as both left hippocampal volume and resting-state RSA were previously found to moderate associations between adversity and psychological function. Highlights: Larger left hippocampal volume associated with higher resting-state RSA. No association between amygdala and right hippocampal volume and resting-state RSA. Left hippocampal volume in early life may convey risk for difficulties in emotion processing and related mental health.